HIV Co-infection Augments EBV-Induced Tumorigenesis in vivo - Whitehurst, Christopher B.; Rizk, Monica; Teklezghi, Adonay; Spagnuolo, Rae Ann; Pagano, Joseph S.; Wahl, Angela (Frontiers in Virology, 2022)
In most individuals, EBV maintains a life-long asymptomatic latent infection. However, EBV can induce the formation of B cell lymphomas in immune suppressed individuals including people living with HIV (PLWH). Most individuals who acquire HIV are already infected with EBV as EBV infection is primarily acquired during childhood and adolescence. Although antiretroviral therapy (ART) has substantially reduced the incidence of AIDS-associated malignancies, EBV positive PLWH are at an increased risk of developing lymphomas compared to the general population. The direct effect of HIV co-infection on EBV replication and EBV-induced tumorigenesis has not been experimentally examined. Using a humanized mouse model of EBV infection, we demonstrate that HIV co-infection enhances systemic EBV replication and immune activation. Importantly, EBV-induced tumorigenesis was augmented in EBV/HIV co-infected mice. Collectively, these results demonstrate a direct effect of HIV co-infection on EBV pathogenesis and disease progression and will facilitate future studies to address why the incidence of certain types of EBV-associated malignancies are stable or increasing in ART treated PLWH.